Efektivitas penerapan bimbingan dan konseling oleh guru kelas 1 di MI Al Fattah Malang - Agustin, Novita Tri (Maliki Interdisciplinary Journal, 2024)
The implementation of guidance and counseling by grade 1 teachers at MI Al Fattah Malang has an important role in helping students develop holistically. This article reviews the importance of guidance and counseling by classroom teachers, with a focus on efforts to provide emotional support, overcome behavioral problems, and build student character. The data collection methods used in this article are observation, interviews and documentation. Data analysis has gone through several stages, namely data reduction, presentation and drawing conclusions. The research results show that grade 1 teachers at MI Al Fattah Malang have a significant role in providing guidance and counseling to students. However, there are several obstacles faced, such as limited time and teacher knowledge in the field of guidance and counseling. Therefore, further efforts are needed to improve the understanding and skills of classroom teachers in providing effective guidance and counseling to students in elementary schools.